2006
DOI: 10.1175/ei200.1
|View full text |Cite
|
Sign up to set email alerts
|

Methane Emissions from Natural Wetlands in the United States: Satellite-Derived Estimation Based on Ecosystem Carbon Cycling

Abstract: Wetlands are an important natural source of methane to the atmosphere. The amounts of methane emitted from inundated ecosystems in the United States can vary greatly from area to area. Seasonal temperature,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 30 publications
3
46
1
Order By: Relevance
“…Once these competitive interactions have been accounted for, Eq. (1) is solved using a Crank-Nicholson solver (Press et al, 1989) (Appendix A). Two methane balance checks are performed at each timestep to insure that the diffusion solution and the time-varying aggregation over inundated and non-inundated areas strictly conserves methane molecules (except for production minus consumption) and carbon atoms.…”
Section: Boundary Conditions and Reactive Transport Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Once these competitive interactions have been accounted for, Eq. (1) is solved using a Crank-Nicholson solver (Press et al, 1989) (Appendix A). Two methane balance checks are performed at each timestep to insure that the diffusion solution and the time-varying aggregation over inundated and non-inundated areas strictly conserves methane molecules (except for production minus consumption) and carbon atoms.…”
Section: Boundary Conditions and Reactive Transport Solutionmentioning
confidence: 99%
“…Previous regional and global CH 4 emission models have applied wetland distribution estimates from Matthews and Fung (1987) (e.g., Zhuang et al, 2004;Walter et al, 2001a;Cao et al, 1996), Landsat (Potter et al, 2006), or the IGBP soils database (Wania et al, 2010). However, these static distributions do not allow for prognostic analysis of changes in surface hydrology that may affect CH 4 emissions over the 21st century.…”
Section: Inundated Fraction Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bridgham et al (2006) estimated that CH 4 emission in North America's wetlands is 9 T g CH 4 a −1 . Using a satellite-derived modeling approach, Potter et al (2006) estimated that the CH 4 emission from the natural wetlands in the conterminous US is 5.5 T g CH 4 a −1 . Several studies also reported the fluxes of N 2 O in terrestrial ecosystems at global and regional scales using empirical approaches .…”
Section: Introductionmentioning
confidence: 99%
“…CH 4 emissions from crop agriculture were assumed to follow emissions from the DNDC model for an average climate year with high irrigation as described by Salas et al (2006). CH 4 emissions from wetlands in California were assumed to follow the NASA-CASA estimates from Potter et al (2006). Although some of these sources are expected to vary on a seasonal basis, they do not incorporate temporal variation in current study, which may cause the a priori emissions to be slightly overestimated or underestimated.…”
Section: Rn Emissionsmentioning
confidence: 99%